SWOT Analysis of the Application of Battery-Free Sensor Systems for Smart Infrastructure: A Literature Review on Micro Energy Technology - Dwiyanto, Dwiyanto (Pt. Anagata Sembagi Education, 2025)
The development of smart infrastructure requires sensor systems that can operate autonomously without relying on conventional batteries. This study analyzes the strengths, weaknesses, opportunities, and challenges (SWOT) of implementing battery-free sensor systems based on energy harvesting technology for smart infrastructure through a systematic literature study. The research methodology uses a literature review approach by analyzing 85 indexed international journal articles from the IEEE Xplore, ScienceDirect, SpringerLink, and MDPI databases for the period 2019-2024. The results of the SWOT analysis show that battery-free sensor systems have the main advantages of continuous operation, reduced maintenance costs by up to 60%, and are environmentally friendly. The main disadvantages include the limited energy that can be harvested (0.1-100 µW), dependence on environmental conditions, and the complexity of energy management. The greatest opportunities lie in the growth of the smart city market, which will reach 2.5 trillion by 2025, and the development of low-power communication technologies. Key challenges include fluctuations in environmental energy sources, electromagnetic interference, and data security regulations. This study provides strategic guidance for the development and implementation of battery-free sensor systems in smart infrastructure with energy harvesting efficiency that can be increased up to 85% through design optimization and adaptive energy management algorithms